(untitled) (Revista Direitos Humanos e Democracia, 2025)
This article’s research problem is to investigate whether the use of personal data can harm socially vulnerable groups in Brazil. The hypothesis is that the data collected can reinforce existing social imbalances in the country and increase control over people in vulnerable situations. The text aims to briefly analyze the legislative trajectory on the topic of data protection and storage, in light of the theory of surveillance capitalism (Zuboff, 2019), both at the international level and in relation to Brazilian legislative advances, and then relate social vulnerability in Brazil to the need for personal data protection. The text was structured into two subsections that correspond to its objectives. This research uses the inductive method and is exploratory in nature, anchored in national and international legislation and bibliography. Data from the IBGE and the 2024 Violence Atlas were also used.